City Branding: communication and marketing strategy for an island urban policy - Patricia del-Ponti; Almudena Barrientos-Báez; David Caldevilla-Domínguez (Revista Mediterránea de Comunicación, 2022)
Nowadays, in our so-called “Information Society”, no one can doubt that marketing and communication within a tourist city are crucial for its existence and development. Due to this, city branding research has gained interest in international literature in recent years. The current project focuses on the implementation of a place-branding competitive strategy in the case of Santa Cruz de Tenerife, a medium-sized island capital city, to explore the core mechanism of this phenomenon, from an applied perspective and as a result of the experience gained in several knowledge transfer projects led by the authors. More specifically, this research sought to analyze the current conditions prevailing in the capital of a peripheral island together with possible collaborations between actors. Extended bibliographical research in city branding, as well as successful case studies of other places, led to the formation of the panel discussion. Qualitative research, using in-depth interviews with local stakeholders, public administration opinion leaders and private entrepreneurs, was also carried out. The findings suggest that organizing broad stakeholder participation in the branding process on the site is an inescapable necessity in times of globalization and promoting the territory on the basis of that brand is a major component.